THREE-VARIANT PROCESSING AND ADJUSTMENT OF OBSERVATIONS AND DETERMINED ESTIMATIONS - Labant, Slavomír; Weiss, Erik; Gašinec, Juraj; Zuzík, Jozef; Király, Alexander (GeoScience Engineering, 2014)
The present article deals with three-variant processing and finding estimates of unknown parameters in a geodetic network by the technology of global navigation satellite systems in 2004, 2008 and 2011. The assessment of the impact of a used method of adjustment on the estimation of parameters of the first and second order of the geodetic network and the presentation of results of a deformation analysis with graphical visualisation of individual processing and analyses are the objectives of this paper. An LSM method and robust M-estimates according to Huber and Hampel were used for the processing and adjustment of observations. All three processing methods showed a displacement of point No. 5005 in the epoch 04-08 in the analysis of the stability of points, which is also confirmed by graphical visualisations using confidence error ellipsoids.